Temporal changes in size-at-age: Impacts and implications for reproductive biology, egg density and management of Pacific herring in British Columbia. (January 2019) - Hay, Doug; Schweigert, Jake; Boldt, Jennifer L.; Thompson, Matt
Abstract: Age-specific declines in length and weight of Pacific herring occurred in all coastal areas of British Columbia (BC) from approximately 1985 to 2010, followed by a more recent reversal in that trend. Concurrent with declining age-specific size, the number of egg layers deposited on vegetation, as estimated from diver surveys, declined but recently this trend also has reversed. In most areas egg layers declined by half, or more, of pre-decline estimates, from means of about 2–3 layers to about 0.5–1 layers. In general, as egg density declined, no corresponding reductions occurred in other metrics of herring spawning such as the mean length or width of the spawning bed. Correlation analyses indicate that the coherence of these two independently measured trends (declining size-at-age and declining egg density) is highly significant (p ≪ 0.01) in all REGIONs of the BC coast. We briefly examine two of several potential biological explanations for these temporal changes: (1) size-dependent ovary size; (2) size-dependent packing density of spawning fish. Quantitative estimates of herring spawn deposition are integral to herring spawning stock biomass assessments in BC and elsewhere so it is important to understand the factors that affect egg density. Our analyses indicate that changes in herring growth or 'size-at-age', which probably reflect regional warming related to climate change, can subsequently impact parameters of reproduction and spawning behaviour.